A novel strategy for enhancing the flame resistance, dynamic mechanical and the thermal degradation properties of epoxy nanocomposites. (13th November 2019) - Xue, Yijiao; Shen, Mingxia; Zeng, Shaohua; Zhang, Wei; Hao, Lingyun; Yang, Lu; Song, Pingan
Abstract: In this study, aiming at improving the flame resistance of bisphenol-A epoxy resin (EP), a novel self-assembled montmorillonite-multiwalled carbon nanotube (MMT-MWCNT) was designed and prepared by using triethylenetetramine (TETA) as grafting agent. The chemical component, structure and morphology of the MMT-MWCNT and its corresponding EP nanocomposites were well characterized. It was disclosed that the MMT was intercalated or exfoliated by the grafted MWCNT, and the MWCNT could be better distributed with the presence of MMT as well. The flame resistance analysis revealed that as compared with the pure EP, the peaks of heat release rate (HRR), smoke production rate (SPR) and carbon monoxide release rate (CORR) of EP/MMT-MWCNT decreased by 7.4%, 26.3% and 13.9%, respectively. The time to ignition (TTI) of EP nanocomposites showed increase compared to pure EP, especially for EP/MMT-MWCNT with an increase by 65.9%. The activation energy (Ea ) and the integral procedural decomposition temperature (IPDT) of the EP/MMT-MWCNT based on TGA were found to be 9.7% and 14.1% higher than those of EP, respectively. Furthermore, the EP/MMT-MWCNT exhibited superior mechanical performance against the EP, that is the storage modulus and loss factor of EP/MMT-MWCNT were increased by 21.5% and decreased by 34.2%, respectively. This novel self-assembled MMT-MWCNT performed advantage over simply mixing MMT and MWCNT in enhancing the flame resistance, dynamic mechanical and the thermal degradation properties of EP.